Nature, nurture and epigenetics. - Crews, David; Gillette, Ross; Miller-Crews, Isaac; Gore, Andrea C; Skinner, Michael K (Mol Cell Endocrinol, 2014)
Real life by definition combines heritability (e.g., the legacy of exposures) and experience (e.g. stress during sensitive or 'critical' periods), but how to study or even model this interaction has proven difficult. The hoary concept of evaluating traits according to nature versus nurture continues to persist despite repeated demonstrations that it retards, rather than advances, our understanding of biological processes. Behavioral genetics has proven the obvious, that genes influence behavior and, vice versa, that behavior influences genes. The concept of Genes X Environment (G X E) and its modern variants was viewed as an improvement on nature-nurture but has proven that, except in rare instances, it is not possible to fractionate phenotypes into these constituent elements. The entanglement inherent in terms such as nature-nurture or G X E is a Gordian knot that cannot be dissected or even split. Given that the world today is not what it was less than a century ago, yet the arbitrator (differential survival and reproduction) has stayed constant, de novo principles and practices are needed to better predict what the future holds. Put simply, the transformation that is now occurring within and between individuals as a product of global endocrine disruption is quite independent of what has been regarded as evolution by selection. This new perspective should focus on how epigenetic modifications might revise approaches to understand how the phenotype and, in particular its components, is shaped. In this review we summarize the literature in this developing area, focusing on our research on the fungicide vinclozolin.
Keywords: Androgen Antagonists; Animals; Corticosterone; DNA Methylation; Endocrine Disruptors; Environment; Environmental Exposure; Epigenesis, Genetic; Female; Fungicides, Industrial; Gene Expression; Gene-Environment Interaction; Genetic Predisposition to Disease; Humans; Male; Oxazoles; Rats; Rats, Sprague-Dawley